Mediterranean Diet, Its Components, and Amyloid Imaging Biomarkers - Vassilaki, Maria; Aakre, Jeremiah A; Syrjanen, Jeremy A; Mielke, Michelle M; Geda, Yonas E; Kremers, Walter K; Machulda, Mary M; Alhurani, Rabe E; Staubo, Sara C; Knopman, David S; Petersen, Ronald C; Lowe, Val J; et al. (Journal of Alzheimer's disease, 2018)
BACKGROUND: There is accumulating evidence suggesting that diet may play a role in preventing or delaying cognitive decline and dementia, but the underlying biological mechanisms are not well understood. OBJECTIVES: To examine the cross-sectional associations of the Mediterranean diet (MeDi) and its components with 11C-PiB-PET scan measures of amyloid-β (Aβ) deposition. METHODS: The study consisted of 278 Mayo Clinic Study of Aging participants 70+ years old, who were cognitively unimpaired (CU) at the time of completion of the Food Frequency Questionnaire (FFQ) and when they underwent PET imaging. Adherence to the MeDi was assessed by computing the MeDi score for each participant. All scans were performed after the FFQ completion; median [IQR] time between FFQ and Aβ PET was 3.5 (1.4) years. Z-scores were created for component, macro- and micronutrients measured. Linear and logistic regression models were adjusted for age, sex, education, apolipoprotein E (APOE) ɛ4 allele carrier status, time interval between the FFQ completion and PET scan, and total energy intake. RESULTS: Participants' median age at FFQ was 77.7 years (55.8% men; 26.6% with an APOE ɛ4 allele). Higher MeDi score (linear regression slope (beta):-0.035, p = 0.012; per standard deviation increase), vegetable intake (beta:-0.043, p = 0.002), intake of vitamin A (beta:-0.041, p = 0.003) or β-carotene (beta: -0.039, p = 0.005) from food sources and moderate alcohol consumption (beta: -0.074, p = 0.03) were associated with lower 11C-PiB standardized uptake value ratio. CONCLUSION: Findings are consistent with previous studies suggesting that higher adherence to a MeDi pattern and higher vegetable consumption are associated with better neuroimaging biomarker profile. Prospective studies are needed to validate current findings.
Keywords: Surveys and Questionnaires; mozek; Humans; neuropsychologické testy; demence; cross-sectional study; kohortové studie; Female; Aged; Psychiatric Status Rating Scales; senioři; lidé; amyloid; průzkumy a dotazníky; Cohort Studies; vegetables; Amyloid; thiazoly; Diet, Mediterranean; Neuropsychological Tests; ženské pohlaví; Aniline Compounds; psychiatrické posuzovací škály; Male; Brain; Cognitive Dysfunction; aniliny; Aged, 80 and over; Dementia; Cross-Sectional Studies; strava středomořská; Positron-Emission Tomography; senioři nad 80 let; Thiazoles; mužské pohlaví; prospektivní studie; pozitronová emisní tomografie; kognitivní dysfunkce; průřezové studie; Mediterranean diet; Prospective Studies